Prediction method and distribution characteristics of in situ stress based on borehole deformation—A case study of coal measure stratum in Shizhuang block, Qinshui Basin - Fang, Xinxin; Feng, Hong; Wang, Yunhong; Fan, Tao (Frontiers in Earth Science, 2022)
Based on the basic theory of elasticity, the geometric equation of borehole deformation under stress was deduced, further the quantitative relationship between the in-situ stress and the geometrical parameters of borehole deformation, then the in-situ stress prediction model based on the deformation of borehole was proposed. Subsequently, numerical simulation on the borehole morphology in different lithologies under in-situ stress was performed to analyze the deformation effect. Logging parameters that are sensitive to the shear wave time difference such as the longitudinal wave time difference, density and natural gamma are selected to be trained with artificial neural network to predict the shear wave time difference. The results show that: 1) Combining theoretical derivation and numerical simulation, the borehole geometry under stress is quasi-elliptic; 2) Compared with the existing shear wave time difference curve, the predicted one by artificial neural network is consistent with the actual ones. Compared with the tested data with acoustic emission, the overall error of the in-situ stress predicted with new method is less than 9.2%, among them, the accuracy of coal seam is the highest with average error of maximum and minimum horizontal principal stress 2.01% and 2.56%, which confirms the feasibility of the method proposed.